Generational Gaps in Media Trust and its Antecedents in Europe. (July 2022) - Brosius, Anna; Ohme, Jakob; de Vreese, Claes H.
We test generational differences in media trust and its antecedents, including political trust, interest, and orientation, as well as perceptions of media inaccuracy and media bias. We rely on original survey data from ten European countries, collected in 2019. We find no differences in the levels of media trust between generations, but we find that key correlates of media trust relate differently to it in different generations. For example, political interest is more strongly correlated with media trust for Millennials than for other generations. Perceptions of bias and inaccuracy have a strong negative correlation with media trust overall, but it is stronger for older generations. These results suggest, that in the long term, societal developments, and in particular debates about media bias and misinformation may impact media trust of young generations differently as they grow older—however, our data give no indication of that creating generational gaps in media trust.